Survey on Current Postnatal Surgical Management of Myelomeningocele in Germany - Mauer, Uwe Max; Jahn, Arne; Unterreithmeir, Luise; Wagner, Wolfgang; Kunz, Ulrich; Schulz, Chris (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2016)
Background and Study Aims Although postnatal surgery can be regarded as the standard of care for open myelomeningocele (MMC), there is no uniform treatment for this condition in Germany. This study assessed the current situation regarding the management of open MMC, a first and essential step toward the development of standards of practice.Patients and Methods In the second half of 2009, we had sent standardized questionnaires to 139 neurosurgery departments and 73 pediatric surgery departments (number of returned questionnaires: 98 and 62, respectively) to identify the principles of MMC management. Newborns with open MMC are treated in 57 of the neurosurgery departments and in 18 of the pediatric surgery departments.Results Overall, 41 of the 57 neurosurgery departments and 16 of the 18 pediatric surgery departments providing care for newborns with MMC perform MMC closure within 24 hours of delivery. In 52 neurosurgery departments and 15 pediatric surgery departments, infants with spina bifida are delivered by planned cesarean section. The diagnostic investigations performed between the time of caesarean delivery and plastic surgical closure vary from none to magnetic resonance imaging of the spine. The criteria underlying the placement of shunts and the time to plastic surgical closure are highly variable.Conclusions The type of treatment that infants with open MMC receive in Germany differs from institution to institution. Clear and consistent guidelines must be established using an interdisciplinary approach to improve treatment and standardize the care provided by surgical specialists for infants with MMC.
Keywords: myelomeningocele; spina bifida; pediatric surgery; neurosurgery